2018
DOI: 10.1155/2018/6349790
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Sleep Apnea in the Canadian Population

Abstract: Older age, obesity, hypertension, snoring, and excessive daytime sleepiness have been associated with sleep apnea. The objective of this study was to determine the prevalence (crude and adjusted), as well as the risk factors, of sleep apnea in the adult Canadian population. Data from the 2009 Sleep Apnea Rapid Response (SARR) questionnaire were used to identify the risk factors, and all sleep-related questions in the SARR questionnaire were used. The outcome variable of interest was health professional-diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 85 publications
0
8
0
3
Order By: Relevance
“…Specifically, OSA is known to affect uncontrolled HTN; however, it remains unclear how HTN affects the incidence or severity of OSA, as well as the risk factors for OSA. Some studies have reported HTN as a risk factor or predictor for OSA [30][31][32]; with certain medications for controlling HTN affecting OSA severity [33]. Further, the similarity of risk factors between HTN and OSA, including age, male sex, and obesity, may have influenced the analysis of HTN as a risk factor of OSA.…”
Section: <A Clinical Formula With Physical Examination Factors>mentioning
confidence: 99%
“…Specifically, OSA is known to affect uncontrolled HTN; however, it remains unclear how HTN affects the incidence or severity of OSA, as well as the risk factors for OSA. Some studies have reported HTN as a risk factor or predictor for OSA [30][31][32]; with certain medications for controlling HTN affecting OSA severity [33]. Further, the similarity of risk factors between HTN and OSA, including age, male sex, and obesity, may have influenced the analysis of HTN as a risk factor of OSA.…”
Section: <A Clinical Formula With Physical Examination Factors>mentioning
confidence: 99%
“…To our knowledge, the current study is substantially larger than any similar study published to date. 24,37,38 We found that most forms of physical activity had a significant protective association with OSA prevalence, independent of potential confounding covariates including BMI. The subtypes of physical activity were assessed separately; increased walking and vigorous-intensity activity were both associated with reduced OSA prevalence.…”
Section: Principal Findingsmentioning
confidence: 79%
“…Combined, an estimated 5.4 million adults have been diagnosed with sleep apnea or are at high risk of developing it (1). Sleep apnea is characterized by repeated cessation of breathing due to a lack of airflow during sleep (2). Of the many types of apneas, obstructive sleep apnea (OSA) is the most common.…”
Section: Main Textmentioning
confidence: 99%